2021
DOI: 10.4166/kjg.2021.071
|View full text |Cite
|
Sign up to set email alerts
|

Acute Abdominal Pain due to Accessory Splenic Infarction in an Adult: A Case Report

Abstract: Accessory spleens are common congenital anatomic variations that are usually asymptomatic. On the other hand, they can be clinically significant if complicated by hemorrhage, torsion, or infarction. This paper describes a case of an infarcted accessory spleen in a 30-year-old male who presented with abdominal pain. Abdominal CT and MRI revealed an isolated mass, 4.5 cm in size, in the perisplenic area. An infarcted accessory spleen was suspected. The patient underwent laparoscopic accessory splenectomy. Histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Accessory spleens are most commonly found in the splenic hilum (75-90% of cases) and the tail of the pancreas. Accessory spleens are the most commonly encountered forms of developmental variations of the spleen [9]. The incidence of accessory spleens at autopsy is 10-30% in the American population and 4.5-24.3% in the Asian population [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessory spleens are most commonly found in the splenic hilum (75-90% of cases) and the tail of the pancreas. Accessory spleens are the most commonly encountered forms of developmental variations of the spleen [9]. The incidence of accessory spleens at autopsy is 10-30% in the American population and 4.5-24.3% in the Asian population [10].…”
Section: Discussionmentioning
confidence: 99%
“…An infarcted accessory spleen manifested as hypointense and hyperintense focus on T1WI and T2WI, and, interestingly, a thin peripheral hyperintense rim was found in all cases on T2WI. Seo and coworkers suggested that it was representative of fibrosis [9]. However, no fibrous tissue was found in pathological specimens of Pérez's cases, and it was proposed that the hyperintense rim could be caused by methemoglobin degraded from hemoglobin during the evolution of infarcted areas or slow blood flow in the residual capsular or subcapsular vasculature [14].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the accessory spleen has no clinical symptoms and is mostly detected by physical examination or other examinations ( 20 ). Currently, it is believed that the accessory spleen needs no special treatment and requires resection only for rupture, infarction or vascular torsion that causes corresponding clinical symptoms ( 21 ). Additionally, the normal spleen and accessory spleen need to be resected together in the treatment of haematological diseases, such as idiopathic thrombocytopenic purpura, otherwise may cause recurrent disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%